Geographic Analysis of Children with Obesity in Kut District (A Study in Population Geography) - Dr. Naji Sahm Rasan; Dr. Mohsen Mansour Sarih (Journal of College of Education, 2025)
The study aims to investigate the prevalence of obesity among male children aged (6-15) years in Al-Kut district, and to identify their characteristics as well as those of their families. It also seeks to determine the main factors contributing to the emergence of this phenomenon and its negative consequences. The study revealed that the obesity rate in Al-Kut district reached 22.1% of the total number of children in the district. The study also found that the percentage of obese children in urban areas is higher than in rural areas. The study highlighted the relationship between several factors and obesity, including economic, social, and genetic factors such as the mother’s occupation, genetic factors, and the child’s freedom from family constraints after joining school. Furthermore, the study revealed the most significant negative consequences of obesity, including chronic diseases such as hypertension and respiratory distress, as well as exposure to bullying and its resulting conflicts and increased bullying rates, which led to a suicide attempt by one of the children in the study sample